Regulation of Maintenance in Islamic Family Law: Implications for Family Welfare - Nizam Ubaidilah; Asmaul Husna (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
The regulation of maintenance in Islamic family law plays a pivotal role in promoting family welfare by ensuring financial and emotional support for dependents. Rooted in Siyasah Syar'iyyah, this framework aligns with the principles of justice, compassion, and shared responsibility. Its implementation influences economic policies that safeguard the rights of vulnerable family members, particularly women and children, fostering societal stability. Furthermore, the integration of Islamic Banking and Sharia Compliance enhances the financial infrastructure to support maintenance obligations through ethical financing solutions. By adhering to Financial Ethics, this system provides equitable mechanisms to address disputes, ensuring fairness while upholding the moral tenets of Islamic law. Challenges, including modern economic pressures and cultural interpretations, highlight the need for adaptive reforms and broader public awareness. Strengthening these regulations within contemporary contexts can profoundly impact family welfare and overall social harmony.